The Synthesis of ZnO Nanostructures as an Effective Photoanode for the Applications of Dye Sensitized Solar Cells : ZnO Nanoflower, ZnO Nanorod, ZnO Nanoball - Manickavasagar, Jeevya; Amira Saryati Ameruddin (Enhanced Knowledge in Sciences and Technology, 2024)
The field of dye-sensitized solar cells (DSSCs) has garnered significant attention due to its potential as a clean and sustainable energy source. This research focuses on the synthesis of ZnO nanostructures to enhance the performance of DSSCs. Three distinct ZnO nanostructures are synthesized utilizing the hydrothermal method and precipitation, aiming to investigate their suitability as photoanodes for DSSCs. The primary objective of this project is threefold. Firstly, to employ the hydrothermal method and precipitation for the synthesis of three types of ZnO nanostructures. Secondly, to fabricate ZnO nanostructured layers as photoanodes using the doctor blade method, and subsequently analyze surface morphology, optical absorbance, and transmittance. Lastly, to characterize the electrical properties of ZnO nanostructured photoanodes using Field Emission Scanning Electron Microscopy (FESEM), UV-vis spectroscopy, and 4-point probe measurements. The hydrothermal method, conducted in an autoclave, is employed for the synthesis of ZnO nanostructures, ensuring precise control over their morphological characteristics. Doctor blade method is emplyed as coating method on the FTO glass The fabricated ZnO nanostructured photoanodes are comprehensively analyzed using FESEM, UV-vis spectroscopy, and 4-point probe measurements to assess their surface morphology, optical properties, and electrical characteristics, respectively. The results reveal crucial insights into the effectiveness of ZnO nanostructured photoanodes for DSSCs. The synthesized nanostructures exhibit distinct morphologies and optical characteristics, providing a basis for understanding their potential in enhancing the overall efficiency of DSSCs. This research contributes to the ongoing efforts in advancing renewable energy technologies by providing a detailed analysis of ZnO nanostructures as promising photoanode materials for DSSCs